Structure-function relationship of DEF6 - Cheng, Huaitao (2018)
DEF6 (Differentially Expressed in FDCP 6, also known as IBP and SLAT) is critical for the development of autoimmune disease and cancer. In T cells, DEF6 participates in TCR-mediated signalling determining T helper cell-mediated immune responses. In addition, DEF6 acts as a guanine nucleotide exchange factor (GEF) for Rho GTPases facilitating F-actin assembly and stabilisation of the immunological synapse (IS). However, DEF6 is also a component of mRNA processing bodies (P-bodies) linking it to mRNA metabolism. DEF6 and its only relative switch-associated protein-70 (SWAP70) share a common domain structure that is highly conserved from human to trichoplax adhaerens suggesting an ancestral function that is distinct from its role in T cell immunity. To further dissect the structure-function relationship of DEF6, a comprehensive analysis of wild type and mutant DEF6 proteins expressed in either COS7 or Jurkat T cells was conducted. The results demonstrate that DEF6 can adopt multiple conformations that result in different cellular localisations and functions. Post translational modifications such as phosphorylation result in conformational change liberating functional domains that are masked in the native state of DEF6. ITK phosphorylation of Try210/222 liberates the N- terminal end and to a certain extend also the C-terminal coiled coil domain of DEF6 resulting in P-body colocalisation. In fact, the N-terminal 45 amino acids of DEF6 that forms two Ca2+-binding EF hands are sufficient to target P-bodies. The coiled coil domain in conjunction with the N-terminal end is facilitating dimerisation and oligomerisation of DEF6 likely to be essential for GEF activity which was mapped to amino acids 537-590, a region that includes the C-terminal end of the coiled coil domain. Mutant proteins that unleashed the coiled coil domain spontaneously aggregated forming large structures in the cytoplasm. These aggregates trapped proteins such as the P-body component DCP1. In some cases, aggregates appeared to function like prions enforcing conformational change onto wild type as well as mutant DEF6 proteins. Ectopically expressed DEF6 colocalised with F-actin in cell protrusions as well as with P-bodies in resting Jurkat T cells. Upon TCR-mediated activation, wild type and several mutant DEF6 proteins were recruited to the IS. However, while wild type DEF6 localised to the central supramolecular activation cluster (cSMAC), mutant DEF6 with disrupted coiled coil domain were present in the outer ring of IS suggesting that recruitment of DEF6 to the cSMAC depends upon a functional coiled coil domain. In contrast, recruitment to the IS of DEF6 that seemed to be mediated through cellular protrusion contacting the antigen presenting cell was independent of both the N-terminal end and a functional coiled coil domain. Taken together, the data presented provide evidence that DEF6 is more than a GEF linking TCR-mediated signalling with F-actin organisation and control of mRNA metabolism.